Cross-sectoral professional relationships and transition to school: an Australian study. Issue 5 (20th October 2021) - Nolan, Andrea; Kilderry, Anna; Chu, Celine
ABSTRACT: Research highlights the importance of seamless transitions between early childhood services and schools to ensure a positive start to school for young children. Drawing on an ecological model of transition where positive outcomes for children depend on the relationships formed between key players in their transition, this paper examines cross-sectoral relationships between the professionals involved. It categorises interactions taking place within the transition then utilises Bourdieu's field theory to explore and illuminate the social processes involved in the pre-school/school relationships. Data are drawn from field visits and interviews with early childhood teachers at 12 services and primary school teachers in 11 schools across the state of New South Wales, Australia. The findings show that not all categories of professional relationships are apparent when classified through transition activities, with personal experiences and historical positionings accounting for such differences. This paper argues that more effort and support is required to build collaborative partnerships that move from being unidirectional to mutually respectful and responsive. This move will enable teachers to engage in professional dialogue and build sustainable professional networks; however, for this to occur teachers need to become aware of how their practices have been shaped by their habitus, capital and the field.